Lakota noon : the Indian narrative of Custer's defeat - Michno, Gregory, 1948- (Missoula, Mont. : Mountain Press Pub., 1997)
Describes the Battle of the Little Bighorn from the Native American point of view.
Includes bibliographical references (p. 317-330) and index.
Keywords: Little Bighorn, Battle of the, Mont., 1876 -- Personal narratives; Cheyenne Indians -- Wars, 1876 -- Personal narratives; Dakota Indians -- Wars, 1876 -- Personal narratives